Building an online platform for ideological and political education resources to promote the development of ideological and political curriculum in medical school - HUANG Fumin, GAO Xiaohui, LIANG Guo, YAN Hongyu (Jichu yixue yu linchuang, 2023)
It is an important mission of medical schools in the new era to cultivate high-quality talents with social responsibility and patriotism family, humanistic qualities, innovative spirit, practical skill and global vision, to be socialist qualified builders and reliable successors with all-round development of moral, intellectual, physical, aesthetic and labor. The ideological and political construction of the curriculum is an necessary pathway for medical schools to improve the professional quality of medical students and cultivate medical workers with good medical ethics and medical style, and is of far-reaching significance for cultivating the health guardians and successors of the medical and health undertakings with skills, feelings and responsibilities. This article raises some suggestions for the ideological and political construction integrated into medical school courses from the perspective of building an online platform as an ideological and political teaching resources for students.